Environmental tax differentiation between industries and households - implications for efficiency and employment: a multi-sector intertemporal CGE analysis for Germany - Christoph Böhringer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
This paper investigates the economic impacts of environmental tax reforms designed to reach given emission reduction targets for the German economy. Our focus is on the efficiency and employment implications of alternative schemes for emission tax differentiation between the production sector and the household sector. We point out that strong tax discrimination in favor of the production sector may cause substantial excess costs. Differences in the emission tax base and the respective ease of emission mitigation across the production sector and the household sector are shown to play a crucial role for explaining our results.
Keywords: H21; D58; Q48; 330; environmental taxes; taxing production vs. taxing consumption; environmental tax reforms; computable general equilibrium; Ökosteuer; Umweltabgabe; Steuerwirkung; Industrie; Steuerbegünstigung; Beschäftigungseffekt; Allgemeines Gleichgewicht; Deutschland